20. The Isolation of Salmonella sp. on quail eggs (cortunxi-cortunix japonica) that failed to hatch in Garot, Darul Imarah Subdistrric, Aceh Besar - Latifa Suryandari; Erina Erina; Darniati Darniati; Safika Safika; Nuzul Asmilia; M. Nur Salim (Jurnal Medika Veterinaria, 2018)
The study aimed to isolate the Salmonella sp on quail eggs that failed to hatch in Garot village, Darul Imarah Subdistrict, Aceh Besar. A total of thirty quail eggs that failed to hatch were examined in microbiology laboratory of Veterinary Medicine Faculty, Syiah Kuala University. Modification of Carter method was used in this study to isolated samples. The eggs were opened for taking the embryo and then it was swabbed with sterile swabs.  The swab was put into Selenite Cystine Broth (SCB) and incubated at 37o C for 24 hours. The breed was then transferred onto Salmonella Shigella Agar (SSA). The growing Bacteria were observed for their morphology and Gram staining to make sure the bacteria belonged to the negative Gram. The result showed that 10 of the 30 of quail eggs that failed to hatch were positively infected with Salmonella sp. Based on this study, it can be concluded that the salmonella sp.can be isolated from quail eggs which were not hatched in the farm of Garot, Darul Imarah Subdistrict, Aceh Besar